2021
DOI: 10.1155/2021/8842522
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus Complicated by Dysautonomia: A Case Report and Review of Management

Abstract: Tetanus is a life-threatening infectious neurological disorder that is now a rare disease due to the institution of wide-spread vaccination strategies. We present an uncommon case of generalized severe tetanus with consequent respiratory failure requiring mechanical ventilation, which was associated with dysautonomia. A 20-year-old unvaccinated female presented with neck stiffness and diffuse muscle spasms following a laceration sustained 3 weeks prior. She was admitted to the intensive care unit for mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In contrast to this finding, primarily hypotension is described in previous case reports (9,16). In human patients, clinical signs of autonomic dysfunction range from profound hypertension and tachycardia to bradycardia, arrhythmia, and hypotension (35). Elevated serum levels of norepinephrine, with spikes of epinephrine levels, cause a hyperdynamic circulatory state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this finding, primarily hypotension is described in previous case reports (9,16). In human patients, clinical signs of autonomic dysfunction range from profound hypertension and tachycardia to bradycardia, arrhythmia, and hypotension (35). Elevated serum levels of norepinephrine, with spikes of epinephrine levels, cause a hyperdynamic circulatory state.…”
Section: Discussionmentioning
confidence: 99%
“…Excess acetylcholine may contribute to this autonomic dysfunction (37). Possible mechanisms of bradycardia are sudden withdrawal of catecholamines or increased vagal tone (35). In human patients, autonomic storms are often followed by severe resistant hypotension, bradycardia, and asystole and result in massive fluctuations in systemic vascular resistance index, with little change in cardiac index (37).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies in the review showed that magnesium sulfate was effective in controlling dysautonomia, especially cardiac arrhythmia or heart block, compared with the non-magnesium group. There are recently reported cases where magnesium sulfate was used successfully alongside other supportive medications to treat dysautonomia in tetanus patients [24,25]. Although the exact mechanism is unclear, magnesium sulfate perhaps helps in controlling dysautonomia by decreasing calcium availability at presynaptic terminals, thereby preventing the release of catecholamines.…”
Section: Discussionmentioning
confidence: 99%